The analysis of sports results obtained by pupils in Primary Schools Championships in Katowice in swimming in the years 2012 - 2016 - Anna Gniezińska; Karol Bar (Kazimierz Wielki University, 2018)
Aim of study: The objective of the study was to analyze the sports results of pupils from primary schools in Katowice over five years. Methodology: The research was conducted in the years 2012-2016. Results were gathered over the last five years from the pupils swimming competitions in primary schools in Katowice. The study included together 290 third grade pupils aged 8-10 years old and sixth grade girls and boys aged 12-13 years old. The research was conducted on a 25 m swimming pool in Interschool Sports Centre in Katowice. For the research were used the method of data analysis documentaries. Secondary data sets have been examined. The results of the 25m freestyle and 50m freestyle swimming competition held in 2012-2016 have been analysed. Results: For the analysis of obtained data were used statistics descriptive which include the mean ± standard deviation (SD), Min-Max range, the coefficient of variation, skewness and kurtosis, an analysis of variance (ANOVA). The shape of the trend changes over time and the prediction were made by using regression, setting trends in linear and non-linear. The level of significance 0.05. Conclusions: In the most diverse group of boys occurred in 2011/2012 at a distance of 25 m, and the distance of 50 m. In the group of girls greatest variability was observed in years 2015/2016 at the distance of 25 m and 50 m. The diversity at both distances tested was higher in girls group than in boys. The best average time for the girls was in the years 2013/2014 at a distance of 25 m, and in 2014/2015 at a distance of 50 m. The boys over a distance of 25 m achieved the best average times in the years 2013/2014 and for a distance of 50 m in the years 2012/2013.